Case Study as a Research Method for Analyzing MOOCs - Ramón Montes-Rodríguez (Athabasca University Press, 2019)
Educational research is one of the many fields of knowledge that frequently use case studies as a research method, particularly when applying an interpretive approach. Based on literature reviews and a systematic analysis of current scientific literature, this paper examines the prevalence and characteristics of the case study as a methodology for research on MOOCs. Ninety-two documents were selected from the search results returned by two of the most prestigious scientific databases: Web of Science (WOS) and SCOPUS. Findings showed that (a) even when searching solely for case studies, quantitative research paradigms were more prevalent than interpretive approaches; (b) geographical distribution of these studies was partially biased; (c) case studies were less prevalent in these databases than other empirical investigations on MOOCs; (d) the data collection and data analysis methods most frequently used in the case studies were more aligned with a quantitative approach; and (e) there is still very little instructor-focused research using this methodology. In the light of these findings and their discussion, future directions for research using case study methodology are proposed, given the potential of this method to illustrate certain issues for which other approaches have proved inadequate or insufficient.